Ministerial Decree No.312/2017 Concerning the Amendment of the Electricity Sale Tariff for the year 2017/2018 = قرار وزاري رقم 312 لسنة 2017 بتعديل تعريفة بيع الكهرباء لعام 2017/2018 / Prime Minister. - Egypt. Prime Minister. (2025)
Ministerial decree no. 312 of the year promulgated 6/7/2017 concerning the amendment of the electricity sale tariff for the year 2017/2018 – قرار وزارى رقم 312 لسنة 2017 صادر بتاريخ 6/7/2017 بتعديل تعريفة بيع الكهرباء لعام 2017/2018